A aquisição do sinal do ponto na produção oral do professor e escrita de um menino de nove anos: um estudo sobre a influência dos gêneros textuais e do diálogo professor/aluno em uma perspectiva enunciativa - (:unkn) unknown (Universidade Federal do Pampa, 2015)
This paper aims to present the results of a research on the acquisition of a punctuation mark in the written production of a nine - year - old boy. The focus of the research is a study based on Émile Benveniste's Theory of Enunciation and the related theoretical and analytical proposal by Costa Silva (2007). Data collection and research was carried out in September 2014, and data were collected at Duque de Caxias Elementary School in the city of Dom Pedrito, RS. From the study by Chacon (2003), we understand that the acquisition of punctuation can be influenced by the choices of the textual genres worked by the teacher in the classroom. To this hypothesis, we add the enunciative principle that the forms of teacher / student dialogue in the classroom also influence acquisition. From the elaboration of an enunciative methodology (S.Silva, 2013), composed by the dialectical relation between three instances of discourse, namely, file-scene-testimony, we elaborated the analysis of the materials used (text, dialogues and informal conversation with student). The results of the research indicated that there is a (dis) encounter between the gender worked by the teacher, poem, and the text requested to the student, narrative; there is a (dis) encounter between teacher / student dialogue and the punctuation present in the student text; there is, finally, in the testimony of the student, an encounter and a mismatch between the activities proposed by the teacher and his learning the punctuation mark (point) required for the activity. This result indicates that the acquisition of language is rather a process of constant adjustments (Costa Silva, 2009) than of continuous and cumulative "acquisition" of language functions, as proposed by other theoretical perspectives.
Keywords: Linguagem; Letras; Aquisição da linguagem em perspectiva enunciativa; Produção oral e escrita; Produção oral; Produção escrita; Pontuação; CNPQ::LINGUISTICA, LETRAS E ARTES